Control of a 2-axis scara robot with a flexible forearm - Liu, Yaping. (2008)
In this thesis, issues in the modelling and control design of the tip position trajectory tracking of a two-link SCARA manipulator arm with a flexible forearm are discussed. A control strategy is proposed such that, by an appropriate choice of outputs for the model, a LQG controller can be implemented such that stability can be guaranteed. The control design is based on the theory of decoupling control by input-output linearization, resulting in 2 decoupled subsystems. For the first rigid shoulder arm, PD control is applied. And for the second flexible forearm, LQG is used. Since the state feedback described as Dong Li is hard to implement, output feedback is used in this project. Tracking performance of the LQG controller is investigated. Simulation will be presented to demonstrate the performance of the manipulator. A simulation shows the system can be stable within 6 seconds. Some elements of the experiment on an industrial 2-axis SCARA robot are also discussed.